14.1: PS Design and Chirography Study of Pressure Sensing and Bistable Cholesteric Liquid Crystal Writing Board. (26th August 2021) - Wu, Xiaojuan; Wang, Jiaxing; Zhao, Yu; Ge, Yang; Wang, Jian; Yu, Hongjun; Wang, Xiuliang; Che, Chuncheng; Xue, Hailin
Abstract : Writing board with cholesteric liquid crystal (CLC) will open a chalk‐free and eye‐protected education thanks to its pressure sensing, light reflected, rewritable, bistable, selective and locally erasable characteristics. Here, photo spacer (PS) design and chirography property of CLC writing board were studied. To obtain certain width and uniform writing chirography, PS is designed orderly and located in pixel area without metal line. It was found that with increasing the PS supporting area and decreasing the height of PS (PSH), the width of chirography decreases. This phenomenon was resulted from the mechanism of pressure transmission through PS and CLCs. In addition, with the same supporting area the smaller the PS density, the finer the handwriting. Finally, the central value of the chirography width is controlled at 3 mm in 63.8 inch product.